Теоретические аспекты механизма трансформации бизнес-процессов предприятий и его экономический инструментарий (Путеводитель предпринимателя)
The article reviews the main methodological improvement of the theory, tools in the mechanism of transformation of forms of operation of industrial enterprises in the modern management system.